Toward managed flexibility: The revival of labour inspection in the Latin world. - Piore, Michael J.; Schrank, Andrew (International Labour Review, 2008)
Examining the role of labour inspection in the context of the revival of labour market regulation, the authors distinguish between the Latin model, where inspectors have authority to tailor enforcement to firms' exigencies, and the less flexible United States approach. The Latin model can reconcile regulation with economic flexibility and transform inspectors into the shock troops of a campaign for decent work. But its vulnerability to arbitrary behaviour on their part needs to be addressed through: management of organizational cultures; exposure and systematization of the tacit knowledge underpinning inspectors' judgements; and research into the relationship between labour standards and business practices.